1993
DOI: 10.1002/ajim.4700240103
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study of congenital defects and parental employment in health care

Abstract: Health care workers may be occupationally exposed to known and suspected teratogens including viruses, anesthetic gases, sterilants, mercury, and x-radiation. To assess the risk of congenital defects among offspring of health care workers, we analyzed parental occupational histories for 4,915 case babies with congenital defects, registered during the years 1968-1980 by the Metropolitan Atlanta Congenital Defects Program (MACDP) registry, and for 3,027 control babies born without defects during the same period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 20 publications
(6 reference statements)
3
30
0
5
Order By: Relevance
“…The definition of shift work also varied, with a vague definition provided in one study. 46 Most studies included in the present systematic review primarily focused on assessing exposure occurring any time during pregnancy 3,12,13,[35][36][37][38][39]42,44,47 or exposure in the first trimester. 2,3,5,41,43,46 Exposure during the last menstrual period 41 or around the period of conception 11 was also reported, but some studies failed to identify a specific time window of susceptibility.…”
Section: Assessment Of Occupational Exposuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition of shift work also varied, with a vague definition provided in one study. 46 Most studies included in the present systematic review primarily focused on assessing exposure occurring any time during pregnancy 3,12,13,[35][36][37][38][39]42,44,47 or exposure in the first trimester. 2,3,5,41,43,46 Exposure during the last menstrual period 41 or around the period of conception 11 was also reported, but some studies failed to identify a specific time window of susceptibility.…”
Section: Assessment Of Occupational Exposuresmentioning
confidence: 99%
“…The eligible studies were conducted in the United States, 9,12,40,[43][44][45]47 Finland, 33,46 Sweden, 2,3,34,37,40 Canada, 36 Denmark, 10,38 France, 5,42 Belgium, 39 the Netherlands, 13 and the Czech Republic 14 ( Table 1). The most relevant characteristics of the eligible studies are shown in Table 1.…”
Section: General Overview Of Excluded and Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a number of epidemiologic studies have identified possible associations of parental occupational exposures with birth defects (Cordier et al, 1997;Correa-Villaseñ or et al, 1991Garcia et al, 1998;Khattak et al, 1999;Matte et al, 1993;McMartin et al, 1998;Olshan et al, 1991;Schnitzer et al, 1995;Shaw et al, 1999a,b;Tikkanen and Heinonen, 1992). However, because assessment of parental occupational exposures in these studies was based either on reported industry and job title, which lack information on specific exposures, or on self-reports of exposures to specific agents, which suffer from low sensitivity and potential recall bias (Garcia, 1998;Bauer et al, 1999), it is likely that the exposure groups evaluated included some misclassified subjects and that the observed odds ratios were biased and imprecise.…”
Section: Introductionmentioning
confidence: 98%
“…Most studies include congenital anomalies in general or defects of the central nervous system (CNS) as a group, including neural tube defects. In these studies, some associations have been found for women working in industry, construction, transport and communication (5,6), dental surgeries (7), and nursing (8) and for women exposed to organic solvents (9). Studies on fathers yielded increased risks for painters (lo), agricultural workers (1 I), workers in the food, beverage, wood and textile industries (12), and fathers exposed to low-level radiation (1 3).…”
mentioning
confidence: 99%